Radiosensitising effect of iron oxide‐gold nanocomplex for electron beam therapy of melanoma in vivo by magnetic targeting - Mahshad Mohamadkazem; Ali Neshastehriz; Seyed Mohammad Amini; Ali Moshiri; Atousa Janzadeh (IET Nanobiotechnology, 2023)
Abstract Melanoma is a dangerous type of skin cancer sometimes treated with radiotherapy. However, it induces damage to the surrounding healthy tissue and possibly further away areas. Therefore, it is necessary to give a lower dose to the patient with targeted therapy. In this study, the radio‐sensitising effect of gold‐coated iron oxide nanoparticles on electron beam radiotherapy of a melanoma tumour with magnetic targeting in a mouse model was investigated. Gold‐coated iron oxide nanoparticles were prepared in a steady procedure. The melanoma tumour model was induced in mice. Animals were divided into five groups: (1) normal; (2) melanoma; (3) gold‐coated iron oxide nanoparticles alone; (4) electron beam radiotherapy; (5) electron beam radiotherapy plus gold‐coated iron oxide nanoparticles. The magnet was placed on the tumour site for 2 h. The tumours were then exposed to 6 MeV electron beam radiotherapy for a dose of 8 Gy. Inductively coupled plasma optical emission spectrometry test, hematoxylin and eosin staining, and enzyme‐linked immunosorbent assay blood test were also performed. Gold‐coated iron oxide nanoparticles with magnetic targeting before electron beam radiotherapy reduced the growth of the tumour compared to the control group. Blood tests did not show any significant toxicity. Deposition of nanoparticles was more in the tumour and spleen tissue and to a lesser extent in the liver, kidney, and lung tissues. The synergistic effect of nanoparticles administered by the intraperitoneal route and then concentrated into the tumour area by application of an external permanent magnet, before delivery of the electron beam radiotherapy improved the overall cancer treatment outcome and prevented metal distribution side effects.